The oral secretion from Cotton Boll Weevil (Anthonomus grandis) induces defense responses in cotton (Gossypium spp) and Arabidopsis thaliana - Stéfanie Menezes de Moura; Kevin Babilonia; Leonardo Lima Pepino de Macedo; Maria Fatima Grossi-de-Sá; Libo Shan; Ping He; Marcio Alves-Ferreira (Current Plant Biology, 2022)
Cotton Boll Weevil (CBW, Anthonomus grandis) is a devastating insect-pest affecting cotton (Gossypium spp), using cotton internal floral structures for larval development, making it difficult to control. Little is known about the mechanism underlying CBW-plant interactions leading to infestation or resistance. Here, we investigated the plant molecular responses triggered by CBW extracts from eggs, larvae, and oral secretions (OS) of larvae and adult. The MAPK pathway, one of the early signaling events in plant pattern-triggered immunity (PTI), was activated by CBW extracts in Arabidopsis thaliana. In cotton, CBW OS activated GhMPK3 and GhMPK6. Importantly, CBW OS activated the PTI marker gene FRK1 and the effector-triggered immunity (ETI) marker gene WRKY46 in Arabidopsis reporter lines, suggesting that Herbivore-Associated Molecular Patterns (HAMPs) present in OS from CBW can elicit plant defense responses in cotton and Arabidopsis. Interestingly, CBW OS-induced MAPK activation shows similar patterns in wild-type and Arabidopsis mutants, which bear mutations in already known receptor and co-receptors complex components, suggesting a distinct signaling cascade likely triggered by the putative HAMPs present in CBW OS. The work points to potentials in the identification and development of CBW extract-derived elicitors for effective pest control combating CBW infestation.